A Highly Integrated Independently Tunable Triple-Band Patch Antenna - Boukarkar, Abdelheq; Xian Qi Lin; Jia Wei Yu; Peng Mei; Yuan Jiang; Yi Qiang Yu (IEEE antennas and wireless propagation letters, 2017)
A highly integrated tunable triple-band patch antenna is designed and fabricated. Two U-slots are cut in the same radiating patch to achieve triple-band performance. While the antenna miniaturization is obtained by loading one patch edge with metalized vias, theory of characteristic modes is adopted to explain the U-slots scaling. The antenna radiating patch size is only 0.1λ 0 × 0.17λ 0 . The operating frequencies can be independently tuned after properly inserting three varactor diodes into the radiating structure. The radiation patterns have similar unidirectional shapes with high stability of the resonant frequencies during the entire tuning of each band. Good agreement between simulation and measurement results is obtained. The antenna covers the following bands: 2.07-2.6 GHz, 2.86-3.57 GHz, and 4.59-5.39 GHz. The measured peak gains and efficiencies are 2.72 dBi and 62.6%, 2.76 dBi and 63.3%, and 2.87 dBi and 66.8%, respectively. Size reduction, multiband function, and independent tuning of three operating bands using only one antenna layer and one RF feedline are combined together to realize a compact and practical antenna.